The Principal's Strategy in Improving the Quality of Human Resource Management with a Humanistic Perspective in the Digitalization Era - Sakarina, Sari; Wedadjati, Ratna Sesotya; Ena, Zet; Hanafiah, Hanafiah; Hina, Hermyn Benny (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2023)
This study aims to describe and analyze the application of a humanistic approach in school leadership, which impacts human resources development in the digitalization era. This research method uses a qualitative approach with a descriptive design. They collect data through participant observation, interviews, and documentation studies to achieve research objectives. A modified analytic analysis method was used to analyze the data. The level of credibility, dependability, transferability, and confirmability are the basis for data validity. The results of the study explain that personal excellence (integrity, wholeness, and self-authenticity) and the humanistic spirituality of inspirational figures inspire the humanistic approach of school principals. The results of this research empirically provide new hope for teachers, staff, students, and parents of students at the elementary level by applying a humanistic approach to school principals in the digital era. This finding has implications, where through a humanistic approach, school principals are more open to appreciating participation and view teachers, employees, and parents as human beings who have equality in building cooperation. Thus, through the humanistic approach of the school principal, the school environment becomes a place for empowering learning and the formation of human values that need to be upheld.